The effect of the guided inquiry learning model on the ability to apply digital engineering concepts at Makassar Aviation Polytechnic - Moch Rifai; Sukarwoto Sukarwoto; Poppy Diana Novitasari (Universitas Negeri Malang, 2025)
This research discusses the importance of implementing humanist parenting patterns and guided inquiry learning models in improving cadet learning outcomes at the Makassar Aviation Polytechnic. A humanist parenting style creates an academic environment that is conducive, democratic, and respects individual uniqueness, to form a professional, ethical, and environmentally conscious character. The guided inquiry model encourages cadets' active and creative participation in the learning process. This method emphasizes independent problem-solving through the scientific process, including problem formulation, hypotheses, analysis, and conclusions. In its application, the teacher provides initial guidance that is gradually reduced so that the cadets are able to carry out independent inquiry. This research aims to determine the effect of the guided inquiry model on cadets' ability to apply digital engineering concepts. The research results show that the guided inquiry model has a significant impact and is more effective than conventional methods. Cadets who use this model demonstrate increased understanding, skills, and active involvement in the learning process. In addition, research finds that creativity does not have a significant effect on learning outcomes, and learning outcomes are determined more by the application of the guided inquiry model. It is hoped that this research can contribute to improving the quality of vocational education in the aviation sector and become a reference for the development of similar research in the future.